The Effect Of Products, Services And Promotions On Decision On Customer Requests On Service Products At Bank BSI Tiban Batam Branch - Sarno; Yandra Rivaldo; Shandrya Victor Kamanda; Edi Yusman (Jurnal Mantik, 2022)
The role of marketing is increasingly important and determines every company, especially bank service companies. The purpose of this study is to determine the influence of products, services and promotions on demand decisions. The population of this study was customers of Bank BSI Tiban Batam Branch which amounted to 582 people. The sample consisted of 86 respondents, which were taken by random sampling method. Data analysis used multiple regression and hypothesis testing and used SPSS version 23. The results of this study concluded that product variables have a significant partial effect on demand decisions, partial service variables have a significant effect on demand decisions, partial promotion variables have a significant effect on demand decisions. Product, service and promotion variables simultaneously have a significant effect on demand decisions.